Faktor Penyebab Hikonka dalam Drama Kekkon Aite wa Chusen de: Analisis Semiotika Charles Sanders Peirce - Ikhwan Ariesta Junaid; Sekar Puji , Meta (Universitas Airlangga, 2024)
The phenomenon of hikonka in Japan, or the tendency of young people not to marry, has been a crucial social issue in Japan since the 1950s, which is heavily influenced by socio-economic and socio-cultural factors. This study aims to reveal the factors causing hikonka through the Japanese drama Kekkon Aite wa Chusen de (2018) using Charles Sanders Peirce's semiotic method. The data analyzed is the main narrative of the drama to identify what factors can be signaled as the cause of hikonka. The research findings show that the hikonka phenomenon in Japan via drama is influenced by the arranged marriage policy imposed by the Japanese government to address the declining birth rate. This policy, which is intended to help overcome hikonka, has the opposite effect, causing social tension because it ignores individual freedom in choosing a life partner. Secondly, the appearance of the main character Miyasaka Tatsuhiko who has obsessive-compulsive disorder (OCD) such as otaku and introvert, which reflects that the occurrence of hikonka in Japan is also affected by the mental health of its youth. Thirdly, hikonka is also influenced by the existence of individuals with diverse sexual orientations, which makes it difficult to find a mate and especially to fulfill the demands of arranged marriages imposed by the government.